Tualang honey supplement improves memory performance and hippocampal morphology in stressed ovariectomized rats - Al-Rahbi, Badriya; Zakaria, Rahimah; Othman, Zahiruddin; Hassan, Asma; Ismail, Zul Izhar Mohd; Muthuraju, Sangu (Elsevier, 2014)
Recently, our research team has reported that Tualang honey was able to improve immediate memory in postmenopausal women comparable with that of estrogen progestin therapy. Therefore the aim of the present study was to examine the effects of Tualang honey supplement on hippocampal morphology and memory performance in ovariectomized (OVX) rats exposed to social instability stress. Female Sprague-Dawley rats were divided into six groups: (i) sham-operated controls, (ii) stressed shamoperated controls, (iii) OVX rats, (iv) stressed OVX rats, (v) stressed OVX rats treated with 17-estradiol (E2), and (vi) stressed OVX rats treated with Tualang honey. These rats were subjected to social instability stress procedure followed by novel object recognition (NOR) test. Right brain hemispheres were subjected to Nissl staining. The number and arrangement of pyramidal neurons in regions of CA1, CA2, CA3 and the dentate gyrus (DG) were recorded. Two-way ANOVA analyses showed significant interactions between stress and OVX in both STM and LTM test as well as number of Nissl-positive cells in all hippocampal regions. Both E2 and Tualang honey treatments improved both short-term and long-term memory and enhanced the neuronal proliferation of hippocampal CA2, CA3 and DG regions compared to that of untreated stressed OVX rats